Pengaruh Social Support terhadap Organizational Citizenship Behavior pada Karyawan wanita di PT. INKA, dengan Work Family Enrichment sebagai variabel mediasi - Amritha, arithea; Sridadi, Ahmad Rizki (Universitas Nahdlatul Ulama Surabaya, 2020)
This research was conducted to examine the effect of Social Support on Organizational Citizenship Behavior on female employees at PT. INKA, with Work Family Enrichment as a mediating variable. The sample used was 62 female employees. The research method used is quantitative to determine the relationship between variables. Exogenous variables, social support, intervening variables are work family enrichment, endogenous variables are OCB. The results of this study are significantly positive effect on Social Support on Organizational Citizenship Behavior with Work Family Enrichment as a mediating variable